Spectroscopic, Thermal Studies and Antimicrobial Activity of Nitrilotriacetates, (NTA)–Ce(III) and –Ce(VI) Complexes - S. Gaballa, Akmal; M. Teleb, Said; S. Asker, Mohsen; A. Soliman, Ahmed (Asian Journal of Chemistry, 2011)
Two new complexes [Ce(NTA)(H2O)2] (1), H[Ce(NTA)(H2O)2]SO4·4H2O (2) were obtained during the reactions of metal salts CeCl3·7H2O and Ce(SO4)2 with nitrilotriacetic acid, H3NTA. The infrared and 1H NMR spectra of the solid complexes have been obtained and assigned. Thermogravimetry, differential thermal gravimetry and differential thermal analyses were also carried out. The data obtained agree quite well with the proposed structures and show that the complexes finally decompose to the corresponding cerium oxides and sulphate. The kinetics of thermal decomposition of the complexes have been studied. The complexes were screened for their antimicrobial activities by the agar-well diffusion technique using DMSO as a solvent against the E. coli, B. subtilis, P. aereuguinosa, S. aureus and fungi: A. niger, A. fluves; C. albican and S. cervisiea. It has been found that the complexes show a considerable antimicrobial activity.